V ZELENI DRŽELI ZELENI BREG: STUDIES IN HONOR OF MARC L. GREENBERG: Ed. Stephen M. Dickey and Mark R. Lauersdorf. Bloomington, Indiana: Slavica Publishers, 2018. 395 pp. - Šabec, Nada (Slavia Centralis, 2020)
December of last year saw the publication of a volume of essays honoring Professor Marc L. Greenberg and his outstanding contribution to the field of Slavic linguistics as well as his role in promoting foreign languages in American higher education.
Keywords: Marc L. Greenberg; linguistics; linguist; V zeleni drželi v zeleni breg; review